Conceptual Design and Analysis of Concentrated Photovoltaic Thermal (CPVT) Solar Collectors with Different Configurations - Sharaf, Omar Z. (2015)
A Master of Science thesis in Mechanical Engineering by Omar Z. Sharaf entitled, "Conceptual Design and Analysis of Concentrated Photovoltaic Thermal (CPVT) Solar Collectors with Different Configurations," submitted in May 2015. Thesis advisor is Dr. Mehmet Fatih Orhan. Soft and hard copy available.